The effect of lemon tea aromatherapy on emesis gravidarum reduction in primigravida trimester I - Nike Sari Oktavia; Dewi Susanti; Revikha Anggalia (Poltekkes Kemenkes Yogyakarta, 2018)
Emesis gravidarum is common in first-trimester pregnancy. Based on the clinical competence of midwifery found cases 86% of the first-trimester pregnant women experience emesis gravidarum. Emesis gravidarum if it can not be given the disturbance of maternal nutrition that will affect the health of mother and fetus. Management of non-pharmacological emesis gravidarum can use lemon tea aromatherapy. The purpose of this research is to know the influence of lemon tea aromatherapy on the reduction of emesis gravidarum in the first-trimester primigravida in Working Area of Pauh Health Centre in Padang 2017. This study was using pre-experiment and with one group pretest-posttest design. This study was done in August 2017 until April 2018in the work area of Pauh Health Centre. The population are first-trimester pregnant primigravida with the sample of the 16, used a technique the sample collection purposive sampling. An instrument used in is sheets of observation and a question. The analysis data consisted of univariate and bivariate using computerized with the dependent t-test. The result of research of average score of emesis gravidarum before treatment that is 4 and after treatment1. After undergone at paired simple obtained the average difference before and after treatment is 3. Ho was rejected with p-value = 0.000 <0.05 it means that there is the influence aromatherapy lemon tea against the reduction of emesis gravidarum in the first-trimester primigravida. The conclusion of this study is there’s the influence of lemon tea aromatherapy on the reduction of emesis gravidarum in the first trimester of primigravida. It is hoped that this research can be an alternative for a midwife in giving nonpharmacologic therapy to reduce the emesis gravidarum complaints in the first-trimester primigravida.